Therapeutic plasma exchange in multiple sclerosis patients with an aggressive relapse: an observational analysis in a high-volume center - Bunganic, R; Blahutova, S; Revendova, K; Zapletalova, O; Hradilek, P; Hrdlickova, R; Ganesh, A; Cermakova, Z; Bar, M; Volny, O (Scientific reports, 2022)
An evidence-based treatment for a Multiple Sclerosis (MS) relapse is an intravenous administration of 3-5 g of Methylprednisolone. In case of insufficient effect or corticosteroids intolerance, the therapeutic plasma exchange (TPE) is indicated. To assess the clinical effect of TPE in treatment of relapse in patients with relapsing-remitting MS (RRMS), we enrolled 155 patients meeting the following criteria (study period: January 2011 to February 2021): (1) age > 18, (2) RRMS according to the McDonald´s 2017 criteria, (3) MS relapse and insufficient effect of corticosteroids/corticosteroids intolerance, (4) baseline EDSS < 8. Exclusion criteria: (1) progressive form of disease, (2) history of previous TPE. Following parameters were monitored: EDSS changes (before and after corticosteroid treatment, before and after TPE; EDSS after TPE was assessed at the next clinical follow-up at the MS Center), and improvement of EDSS according to the number of procedures and baseline severity of relapse. 115 females (74%) and 40 males (26%) were included. The median age was 41 years (IQR 33-47)-131 patients underwent the pulse corticosteroids treatment and TPE, while 24 patients underwent only TPE without any previous corticosteroid treatment. Median baseline EDSS was 4.5 (IQR 3.5-5.5), median EDSS after finishing steroids was 4.5 (IQR 4.0-5.5). EDSS prior to the TPE was 4.5 (IQR 4-6), EDSS after TPE was 4.5 (IQR 3.5-5.5). We observed a significant improvement in the EDSS after TPE (p < 0.001). Sex differences were seen in TPE effectiveness, with median improvement of EDSS in females being -0.5 (IQR 1-0) and in males being 0 (IQR -0.5 to 0), p = 0.048. There was no difference in EDSS improvement by age category: 18-30 years, 31-40 years, 41-50 years, > 50 (p = 0.94), nor by total TPE count (p = 0.91). In this retrospective study of patients with an aggressive relapse and insufficient effect of intravenous corticosteroid treatment, a significant effect of TPE on EDSS improvement was observed. There was no significant difference in TPE effectivity according to the number of procedures, age, nor severity of a relapse. In this cohort, TPE was more effective in females.
Keywords: Young Adult; Recurrence; Male; retrospektivní studie; mladý dospělý; Multiple Sclerosis; Adolescent; hormony kůry nadledvin; Plasma Exchange; Adult; dospělí; relabující-remitující roztroušená skleróza; mužské pohlaví; Multiple Sclerosis, Relapsing-Remitting; výměna plazmy; recidiva; mladiství; lidé; ženské pohlaví; Humans; Adrenal Cortex Hormones; Retrospective Studies; Female; lidé středního věku; roztroušená skleróza; Middle Aged